Comparative study of building fire safety regulations in different Brazilian states. (March 2017) - Rodrigues, Eduardo E.C.; Rodrigues, João P.C.; da Silva Filho, Luiz C.P.
Abstract: In the last forty years, Brazil has seen several major fires resulting in dramatic human and material losses. These led to society-driven initiatives that together with national legislation gaps caused a diversity of building fire safety regulations which were only applicable to the corresponding state. This caused an administrative and technical disarray among fire safety agents, as well as anti-economical building design and construction. This paper presents a comparative study among building fire safety regulations in different Brazilian states aiming at the development and adoption of a technical regulation at a national level. The results showed many differences in regulations on the mandatory requirements for fire protection systems; however, a similar technical base among state regulations showed that a Brazilian national-level fire safety regulation could be created. Highlights: Comparative study among Brazilian fire safety regulations are presented. State regulations showed differences however similar technical base was found. A Brazilian national fire safety regulation could be created.